(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Children are important to the future of society and have the ability to promote social change,economic development, peace and leadership. They play an important role in determining what the worldwill do in future. Children are considered equal members of society and enjoy all such rights as anyother individual will do. Keeping this into consideration the parliamentarians and the laws makes overthe period of time have made special laws to deal with the children who are found in conflict with the law.The Juvenile justice (Care and Protection of Children) Act 2015 is one such act that deals with theinvestigation, trial and rehabilitation of the juvenile delinquents. This being said, one of the mostimportant issue that comes during the whole process is regarding bail to a juvenile. This issue becomesimportant as the on one side an offender needs to be detained in order to protect the society on the otherhand considering the tender age of a child it cannot be denied that custody may do more harm thangood. Keeping in mind this paradox, this article discussed below various aspects of the provisionsregarding bail to the Juveniles and the juxtaposition of High Courts in case of Anticipatory Bail.